2014
DOI: 10.1002/jts.21899
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias Variability and Symptoms of Posttraumatic Stress Disorder

Abstract: Cognitive theories implicate information-processing biases in the etiology of anxiety disorders. Results of attention-bias studies in posttraumatic stress disorder (PTSD) have been inconsistent, suggesting biases towards and away from threat. Within-subject variability of attention biases in posttraumatic patients may be a useful marker for attentional control impairment and the development of posttrauma symptoms. This study reports 2 experiments investigating threat-related attention biases, mood and anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
160
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 37 publications
18
160
3
Order By: Relevance
“…While several studies have examined the effect of attentional bias change from pre- to post-treatment as a mediator of ABM outcomes (Amir, Beard, & Taylor, 2009; Heeren et al, 2012; Kuckertz et al, 2014), this is the first study to suggest that change in attentional bias plasticity may explain positive outcomes resulting from ABM. This is consistent with recent suggestion that variability of attentional bias within session is more directly relevant to PTSD symptoms than attentional bias at a single time point (Iacoviello et al, 2014). One possible interpretation of these results is that individuals who were able to learn through ABM to better control the extent to which their attention was differentially affected by emotional stimuli experienced subsequent reductions in PTSD symptoms, whereas this process did not occur in the ACC group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While several studies have examined the effect of attentional bias change from pre- to post-treatment as a mediator of ABM outcomes (Amir, Beard, & Taylor, 2009; Heeren et al, 2012; Kuckertz et al, 2014), this is the first study to suggest that change in attentional bias plasticity may explain positive outcomes resulting from ABM. This is consistent with recent suggestion that variability of attentional bias within session is more directly relevant to PTSD symptoms than attentional bias at a single time point (Iacoviello et al, 2014). One possible interpretation of these results is that individuals who were able to learn through ABM to better control the extent to which their attention was differentially affected by emotional stimuli experienced subsequent reductions in PTSD symptoms, whereas this process did not occur in the ACC group.…”
Section: Discussionsupporting
confidence: 93%
“…However, recent research suggests that alternate methods of conceptualizing attentional bias may increase our understanding of cognitive processing in anxiety and its effects on anxiety-related behavior. For example, Iacoviello and colleagues (2014) found that variability of attentional bias rather than attentional bias per is correlated with PTSD symptoms. Moreover, this variability in attentional bias differentiated individuals exposed to trauma who did and did not develop subsequent PTSD.…”
mentioning
confidence: 99%
“…Recently, two research groups independently proposed and tested new methods to index individuals’ tendencies to switch their focus of attention towards and/or away from visual emotional information [1,2]. Adding new analysis options for Dot Probe Task (DPT) derived data, these new indices are meant to capture differential dynamics of attention allocation over time.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters (in the college student sample, inter-trial variability of starting point [szr]; in the MTurk sample, inter-trial variability of nondecisional components [st0]; and in the adolescent sample, the threshold separation [a]) relate to inter-trial variability and to reaction times. That is, the valenced parameters already selected for each model contain sufficient information to differentiate between participants based on processing of positive and negative valence; the best method to further explain residual deviance was to use methods that measure differential reaction speeds or differential patterns of response (Iacoviello et al, 2014; but note Kruijt, Field, & Fox, 2016). In Figure 2, it is clear that these parameters do not have significant impact on their own, but only in conjunction with the other variables selected previously in the models.…”
Section: Discussionmentioning
confidence: 99%